Effect of Aerobic Exercise on Oxidative Stress and Inflammatory Response During Particulate Matter Exposure in Mouse Lungs - So, Byunghun; Park, Jinhan; Jang, Junho; Lim, Wonchung; Imdad, Saba; Kang, Chounghun (Frontiers in Physiology, 2022)
Regular exercise provides several health benefits that can improve the cardiovascular and musculoskeletal systems, but clear evidence on the effect of exercise-induced hyperventilation in particulate matter (PM) exposure is still lacking. This study aimed to investigate the effects of exercise in PM exposure on reactive oxygen species (ROS) generation, inflammatory response, and mitochondrial integrity in human lung epithelial cells (A549), as well as in mouse lung tissue. In in vitro experiments, PM treatment was shown to significantly increase ROS production, and reduce cell viability and mitochondrial function in A549 cells. The mice were divided into four groups for an in vivo exercise experiment: control (CON), PM inhalation (PI), PM inhalation during exercise (PIE), and exercise (EX) groups. The PI and PIE groups were exposed to 100 µg/m3 of PM for 1 h per day for a week. The PIE and EX groups performed treadmill exercises every day for 1 h at 20 m/min for a week. The levels of pro-inflammatory markers (IL-6 and TNF-) were significantly higher in the PI group than in the CON group (P<0.001 and P<0.01, respectively). The carbonyl protein level was decreased in EX vs. PI (P<0.001). Mitochondrial fission (Drp1) content was significantly decreased in the EX vs. CON groups (P<0.01), but anti-mitochondrial fission (P-Drp1 Ser 637) was increased in the EX vs. PI groups (P<0.05). Mitochondrial autophagy (mitophagy), which is an assessment of mitochondrial integrity, was markedly increased in PI vs. CON (P<0.001), but the level was reversed in PIE (P<0.05). Lung fibrosis was increased in PI vs. CON group (P<0.001), however, the cells were rescued in the PIE (P<0.001). The number of apoptotic cells was remarkably increased in the PI vs. CON groups (P<0.001), whereas the level was decreased in the PIE (P<0.001). Taken together, these results showed that short-term exposure to PM triggers oxidative stress, pro-inflammatory responses, and apoptosis in the lungs, but the PM-induced adverse effects on the lung tissue are not exacerbated by exercise-induced PM hyperventilation but rather has a protective effect.